Respuesta :
-2x+14=x²-3x+12
add 2x on both side:
14=x²-x+12
subtract 14 on both side:
x²-x-2=0
factor: (x-2)(x+1)=0
x=2 or x=-1
HOPE THIS HELPS AND PLEASE MARK ME AS BRAINIEST AND ADD ME AS A FRIEND
add 2x on both side:
14=x²-x+12
subtract 14 on both side:
x²-x-2=0
factor: (x-2)(x+1)=0
x=2 or x=-1
HOPE THIS HELPS AND PLEASE MARK ME AS BRAINIEST AND ADD ME AS A FRIEND
The resulting equation will be
x^2 - x - 2 =0
x^2 -2x +x -2 = 0
(x-2)(x+1) = 0
x= 2 and x = -1
Hope this will help☺☺
x^2 - x - 2 =0
x^2 -2x +x -2 = 0
(x-2)(x+1) = 0
x= 2 and x = -1
Hope this will help☺☺